Association of Inosine Triphosphatase Polymorphysims rs7270101 and rs1127354 with the occurrence of Anemia in Hepatitis C patients receiving Pegylated Interferon and Ribavirin - Rahman, Inayat Ur (International Journal of Pathology, 2019)
Background: HCV presents major health care problem in Pakistan. Hepatitis C patients if not well treated may progress to liver cirrhosis and cancer. Currently recommended directly acting antiviral drugs produces better cure rate and less adverse effects than earlier drugs peg-interferon and ribavirin. Peg-interferon and ribavirin combination therapy produces anemia in hepatitis C patients which is the main reason for treatment discontinuation or dose reduction. Anemia due to peg-interferon and ribavirin therapy is associated with ITPA polymorphism.Objectives: To find the association of ITPA polymorphisms rs7270101 and rs1127354 with occurrence of anemia in hepatitis C patients receiving peginterferon and ribavirin combination therapy.Methods: DNA was extracted from blood samples of treatment naïve hepatitis C patients. Two SNPs of Inosine triphosphatase rs7270101 and rs1127354 were genotyped by means of allelic inhibition of displacement activity method. Complete blood count of the patients was carried out first before starting interferon and ribavirin therapy and then after three months of therapy.Results: 20 out of 115 patients had more than 3gm/dl reduction in hemoglobin level after 3 months of anti-HCV therapy. At rs1127354, 69 patients showed the presence of CC genotype, 38 were found to have CA and 3 patients had AA genotype. The minor allele A at rs1127354 was found to be protective against anemia due to peg interferon and ribavirin combination therapy in hepatitis C patients (Odds ratio=0.275, C.I= [0.081-0.938], Chi2=4.77, p=0.02889) while the major allele C at rs1127354 was found to be associated with anemia in HCV patients receiving interferon and ribavirin combination therapy (Odds ratio=3.638, C.I= [1.066-12.409],Chi2=4.77, p=0.02889).At rs7270101 all the patients showed AA genotype.Conclusion: The current study concludes that CA/AA genotype at ITPA SNP RS1127354 provides protection against anemia in hepatitis C patients receiving interferon and ribavirin combination therapy.